Knowledge management strengthens decision making: The case of the "Knowledge Center for Assessing Vulnerability to and Impact of Climate Change on the Andes of Colombia, Ecuador, and Peru" - Cunha, Flavia; Staiger Rivas, Simone; Valencia, B.; Pérez Olmedillo, S. (2014)
Under the REGATTA Initiative (Regional Portal for Technology Transfer and Action against Climate Change in Latin America and Caribbean) this project seeks to develop actions towards vulnerability and adaptation to climate change assessment in agriculture and water resources in the Andes of Colombia, Ecuador and Peru. The clear knowledge focus of this project led to the successful creation of an on-line Community of Practice (COP-Andes) through which key project stakeholders of public and private sectors gathered with civil society in order to discuss recommendations and promote debates on local issues and alternatives, using online dialogues and virtual discussion forums.